Uses Of Natural Dyes To Develop Tiga Negeri Batik - Theresia Widyastuti (Institut Seni Indonesia Denpasar, 2024)
Tiga Negeri batik began to be made in the late 18th century on the north coast of Java island but its dyeing process was made in three cities, namely Lasem, Pekalongan, and Surakarta. The term three refers not only to the number of colors but also to the combination of three cultures behind the style, namely Java, China, and Europe. This field research using qualitative methods aims to explore the possibility of developing Tiga Negeri batik through the use of natural coloring from plants. Data were collected through observation and interviews with batik artisans in Lasem, Pekalongan and Surakarta, as well as batik artisans who are also natural dye activists and who are members of the Indonesian Natural Dyers Association living in Kediri and Jombang. The result is that Tiga Negeri batik with environmentally friendly natural dyes can be achieved despite still having to use a small amount of artificial dyes, especially for the red color. This effort to return to natural dyes is mainly because this type of batik attracts the attention of international consumers in particular, and domestic consumers in general.